Ready player one (Terri white, Empire, 2018)
If it's a concern for you, the movie is very clean. Not much for dialogue, so no swearing. No sexual content. I was worried it would have cheesy, unnecessary gore; It does not have that. The blood is pretty mild in my opinion... tasteful seems like a weird word to use for blood. But, uh, tasteful.